2018
DOI: 10.1002/jcb.28234
|View full text |Cite
|
Sign up to set email alerts
|

CREB/Wnt10b mediates the effect of COX‐2 on promoting BMP9‐induced osteogenic differentiation via reducing adipogenic differentiation in mesenchymal stem cells

Abstract: Bone morphogenetic protein 9 (BMP9) is one of the most potent osteogenic factors, which may be a potential candidate for bone tissue engineering. However, the osteogenic capacity of BMP9 still need to be further enhanced. In this study, we determined the effect of Wnt10b on BMP9-induced osteogenic differentiation in mesenchymal stem cell (MSCs) and the possible mechanism underlying this process. We introduced the polymerase chain reaction (PCR), Western blot analysis, histochemical stain, ectopic bone formatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 49 publications
0
14
0
Order By: Relevance
“…In macrophages, the expression of cAMP-responsive element-binding protein (CREB) [ 33 ] inhibits AP1, which are involved in the expression of iNOS, IL6, TNF, and IL1 [ 34 ]. Additionally, CREB expression has been described in MSCs, regulating COX2 function [ 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…In macrophages, the expression of cAMP-responsive element-binding protein (CREB) [ 33 ] inhibits AP1, which are involved in the expression of iNOS, IL6, TNF, and IL1 [ 34 ]. Additionally, CREB expression has been described in MSCs, regulating COX2 function [ 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…Together, we revealed the role of linc02349 as a ceRNA for miR‐25‐3p/33b‐5p. Wnt10b shifts cell fate towards the osteoblast lineage by induction of the osteoblastogenic transcription factors SMAD5, Dlx5 and OSX 25,45,46 . SMAD5 is the gene involving BMP signal and promotes osteogenic differentiation of MSC 26 .…”
Section: Discussionmentioning
confidence: 99%
“…For example, bone morphogenetic protein-2 promotes osteosarcoma growth, BMP5 regulates neural crest cell survival, BMP7 possesses anti-cancer activity through non-canonical BMPs/Smads signaling pathway and BMP9 induces osteogenic differentiation. 17 , 18 , 19 , 20 But there is an uneven distribution of concerns about the various aspects of the role of BMP9 in cancers. 21 , 22 Moreover, it was reported that the anti-cancer activity of Res(resveratrol), which is also isolated from the Chinese herbal medicine, may directly up-regulate BMP9 expression to activate p38 MAPK in colon cancer, 23 so whether BMP9 participates in the anti-cancer effect of Tet has aroused our concern.…”
Section: Introductionmentioning
confidence: 99%